Discrimination of Different Brain Metastases and Primary CNS Lymphomas Using Morphologic Criteria and Diffusion Tensor Imaging - Bette, S.; Wiestler, B.; Delbridge, C.; Huber, T.; Boeckh-Behrens, T.; Meyer, B.; Zimmer, C.; Gempt, J.; Kirschke, J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Brain metastases are a common complication of cancer and occur in about 15 – 40 % of patients with malignancies. The aim of this retrospective study was to differentiate between metastases from different primary tumors/CNS lymphyomas using morphologic criteria, fractional anisotropy (FA) and apparent diffusion coefficient (ADC).Materials and Methods: Morphologic criteria such as hemorrhage, cysts, pattern of contrast enhancement and location were reported in 200 consecutive patients with brain metastases/primary CNS lymphomas. FA and ADC values were measured in regions of interest (ROIs) placed in the contrast-enhancing tumor part, the necrosis and the non-enhancing peritumoral region (NEPTR). Differences between histopathological subtypes of metastases were analyzed using non-parametric tests, decision trees and hierarchical clustering analysis.Results: Significant differences were found in morphologic criteria such as hemorrhage or pattern of contrast enhancement. In diffusion measurements, significant differences between the different tumor entities were only found in ADC analyzed in the contrast-enhancing tumor part. Among single tumor entities, primary CNS lymphomas showed significantly lower median ADC values in the contrast-enhancing tumor part (ADClymphoma 0.92 [0.83 – 1.07] vs. ADCno_lymphoma 1.35 [1.10 – 1.64] P = 0.001). Further differentiation between types of metastases was not possible using FA and ADC.Conclusion: There were morphologic differences among the main subtypes of brain metastases/CNS lymphomas. However, due to a high variability of common types of metastases and low specificity, prospective differentiation remained challenging. DTI including FA and ADC was not a reliable tool for differentiation between different histopathological subtypes of brain metastases except for CNS lymphomas showing lower ADC values. Biopsy, surgery and staging remain essential for diagnosis.Key Points:• Histopathological subtypes of brain metastases/CNS lymphomas show different morphologic features on MRI• Primary CNS lymphomas show significantly reduced ADC values• DTI is not a reliable tool for differentiation between brain metastasesCitation Format:• Bette S, Wiestler B, Delbridge C et al. Discrimination of Different Brain Metastases and Primary CNS Lymphomas Using Morphologic Criteria and Diffusion Tensor Imaging. Fortschr Röntgenstr 2016; 188: 1134 – 1143
Keywords: brain metastases; diffusion tensor imaging; fractional anisotropy; apparent diffusion coefficient